Differentiated Learning Through the Problem-based Learning Model on Scientific Literacy Abilities Based on Students’ Learning Styles on Human Respiratory System - Atikah; Luzyawati, Lesy; Yuliana, Eva (Indonesian Journal of Biology Education, 2025)
Less varied learning models often cause students' low scientific literacy abilities. This research aims to determine whether differentiation learning through a problem-based learning model based on learning styles can improve students' scientific literacy skills in the human respiratory system concept. The research method used in this research is quantitative. The population in this study was class XI MIPA SMAN 1 Lohbener, with a sample of class XI MIPA 5 and XI MIPA 2. The sampling technique uses a random sampling technique. The instrument used is nine multiple choice questions to measure scientific literacy skills using criteria questions C4-C5 adapted to learning indicators, and a learning style instrument includes 14 statements adapted to learning style indicators. After processing the data, the results of the scientific literacy abilities of the experimental class and control class students obtained Sig. 0.728 > 0.05, so there is no difference in scientific literacy abilities based on student learning styles. There is also a difference in scientific literacy abilities between the differentiated and undifferentiated problem-based learning models (Sig. 0.000 < 0.05). Additionally, there is no interaction effect between the problem-based learning model and student learning styles (Sig. 0.944 > 0.05). These results indicate that the learning model is more effective in the learning process for all students, while learning style influences how students absorb the information taught.